A case of livedoid vasculopathy, a thrombotic occlusive vasculopathy - Anais Huot; Christa‐Maria Maniu; Sofia Bogiatzi; Daniel Hohl; Lorenzo Alberio; Gregoire Stalder (Wiley, 2022)
Abstract Livedoid vasculopathy (LV) is a rare thrombotic occlusive vasculopathy presenting with chronic relapsing‐remitting bilateral painful skin ulcerations predominating on the ankles and dorsal surface of the feet. LV can be idiopathic or secondary to endothelial dysfunction, rheological disorder, haemostatic or fibrinolytic pathology. We describe the case of a 49‐year‐old patient with LV and summarise the current knowledge on epidemiology, risk factors, and treatment of this rare condition. It is important to differentiate LV from vasculitic disorders, the management of the latter being based on immunosuppression, whereas the treatment of LV is based on anticoagulant or antiplatelet therapy.